2012
DOI: 10.1037/a0027498
|View full text |Cite
|
Sign up to set email alerts
|

Short message service reduces dropout in childhood obesity treatment: A randomized controlled trial.

Abstract: These results indicate that SMSMT is effective in reducing dropout rates from a pediatric lifestyle intervention. Future research should examine the effectiveness of SMSMT on weight management and related psychosocial variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 44 publications
0
89
0
Order By: Relevance
“…However, control group and e-contact group comparisons were only conducted in the SMSMT study. 31 The other trial 29 compared the results of the e-contact with a group who also received the lifestyle intervention.…”
Section: Study Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, control group and e-contact group comparisons were only conducted in the SMSMT study. 31 The other trial 29 compared the results of the e-contact with a group who also received the lifestyle intervention.…”
Section: Study Interventionsmentioning
confidence: 99%
“…All the eligible seven trials stemmed from only two large RCTs extensively published in the last 5 years: ''The Loozit Ò study'' (n = 5 publications) [25][26][27][28][29] and ''The SMSMT (SMS Management Technics) study'' (n = 2 publications). 30,31 To avoid duplication of data, we included only one RCT from each of the two large trials; the publication selected from these large trials was the one that most closely described the effectiveness of smartphone technology for promoting health-related outcomes.…”
Section: Study Inclusion/exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another intervention utilized a short message service via mobile phones to provide overweight and obese children with personalized feedback and prompts to encourage healthy behaviors [67]. This study did not result in BMI reduction; however, the intervention group had a lower dropout rate and children with the greatest weight loss engaged more actively with the message service [68]. Finally, as part of the protocol of a randomized controlled trial in 3-to 10-year-old children, one paper showcased a technology under development to integrate treatment across settings [69].…”
Section: Treatment Interventionsmentioning
confidence: 99%
“…In one of those studies, clinically reasonable dose of 12 g has been suggested 36) . However, it should be noted that those studies were merely a literary discussion or a clinical study Lifestyle programs can reduce the level of overweight in children [37][38][39][40][41][42] . However, the success of these lifestyle interventions is limited in that maintaining the results and adherence to treatment are difficult to achieve 43) .…”
Section: Asparagus Cochinchinensis Inmentioning
confidence: 99%